Fusion of environmental monitoring components and gardening modules for manipulating indoor air quality. Issue 4 (September 2019) - Chen, J C; Lin, Y J; Yang, Z L; Yu, C C
Abstract: People who live in a crowded jungle of metropolis are easy getting stressed and extremely need relaxing activities, e.g. gardening. The considerations about limited space, busy day and scarce experience will stop people to take action on gardening. They do need a device to help them taking care of plant, a smart device which is able to remotely control would be popular to the business of interior planting. This demand encouraged many designers to create the modules for interior planting. It also pushes researchers to study how interior planting is able to capture particles, to absorb VOC, to transform CO2, to change temperature and moisture. However, planting module with smart control of indoor air quality is rare until now. So we created an environmental manipulator in which environmental monitoring sensors, planting modules, and remote relays are fused together. This study described the process how we get the optimal design of environmental manipulator under a series of interviews based on Evaluation Grid Method (EGM).